Factors Causing Fraud in Hospitals Under National Health Insurance and Prevention Strategies: A Scoping Review - Noor Rachni, Silmi; Permanasari, Vetty Yulianty (BPJS Kesehatan, 2025)
Fraud in the implementation of the National Health Insurance program poses a significant challenge to hospital governance in Indonesia, resulting in financial losses and eroding public trust in healthcare services. We conducted a scoping review to identify the root causes of fraud and summarize prevention strategies applied in hospitals participating in the scheme. The review analyzed literature published between 2022 and 2024, selected through database searches and manual screening, with a focus on fraud-related issues and prevention efforts within healthcare facilities. Findings reveal that multiple factors, including discrepancies between case-based payment tariffs and the actual cost of services, weak internal control systems, limited understanding among staff regarding the accountability of public funds, inadequate reporting mechanisms, and poor organizational ethics, drive fraud. Identified prevention strategies include the establishment of anti-fraud teams, implementation of internal audits, utilization of hospital information systems, staff training initiatives, and intersectoral collaboration. In conclusion, fraud prevention in national health insurance requires a comprehensive approach encompassing institutional policies, human resource capacity building, and the reinforcement of transparent and accountable governance across hospital management systems.